2013
DOI: 10.2147/btt.s47438
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of human monoclonal antibodies generated with peripheral blood lymphocytes from dengue patients with Japanese encephalitis virus

Abstract: BackgroundHybridomas that produce human monoclonal antibodies (HuMAbs) against Dengue virus (DV) had been prepared previously using peripheral blood lymphocytes from patients with DV during the acute and convalescent phases of a secondary infection. Anti-DV envelope glycoprotein (E) 99 clones, anti-DV premembrane protein (prM) 8 clones, and anti-DV nonstructural protein 1 (NS1) 4 clones were derived from four acute-phase patients, and anti-DV E 2 clones, anti-DV prM 2 clones, and anti-DV NS1 8 clones were deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Flavivirus antibodies are known to be highly cross reactive in nature and are known to give false positive responses in antibody detection assays [ 16 , 19 , 20 ] and the higher JEV seropositivity in adults who were hospitalized due to dengue, could possibly be due to higher cross-reactive DENV antibody titres (and therefore JEV antibody titres). Therefore, we determined the association between the optic density (OD) values for DENV and JEV in those with hospitalized dengue and those who had asymptomatic/mild dengue.…”
Section: Resultsmentioning
confidence: 99%
“…Flavivirus antibodies are known to be highly cross reactive in nature and are known to give false positive responses in antibody detection assays [ 16 , 19 , 20 ] and the higher JEV seropositivity in adults who were hospitalized due to dengue, could possibly be due to higher cross-reactive DENV antibody titres (and therefore JEV antibody titres). Therefore, we determined the association between the optic density (OD) values for DENV and JEV in those with hospitalized dengue and those who had asymptomatic/mild dengue.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the detection of the presence of NS1 in the blood is one of the dengue diagnostic methods [ 2 ]. However, the sensitivity of NS1 RDT was ranging from 44.4% to 87% [ 25 28 ] in the detection of DENV when compared to real-time RT-PCR. Besides, the circulating level of NS1 in asymptomatic DENV infections has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found different sensitivities for the SD NS1 RDT, ranging from 44.4% to 87% [ 13 , 20 23 ]. The sensitivity of the CTK NS1 RDT reported by a previous study was 40% [ 24 ], and it has been reported that the RDTs show higher sensitivity with primary infection than with secondary infection samples [ 13 , 24 26 ].…”
Section: Discussionmentioning
confidence: 99%